HAK MILIK ATAS SATUAN RUMAH SUSUN UNTUKPERTOKOAN DARI PERJANJIAN BANGUN GUNA SERAH ATAS TANAH HAK PENGELOLAAN - Rizky Ayu Nataria El Chidtian (Universitas Airlangga, 2013)
Apartments which stand on the land of Freehold Title and Building Rights Title or Right to Use Title on the state land have a clear legal position for the status of apartments. In another case, apartments which stand on the land status of Building Rights Title use above the Right of Management which is also based on the founding treaties Build Operate Transfer (BOT) has the potential dispute in the future if establishment of title to land above Right of Management over the BOT agreement ends. Legal consequences occur when the BOT agreement and Building Rights Title use ends is the existence of apartment unit based on the legal context would be removed. Existences of apartment unit rely in inherent land Building Right Title (HGB) or Right to Use Title (HP). Building Right Title (HGB) or Right to Use Title (HP) have durations of use, and when that period expired, Title to Apartment Unit subject to dismiss.Legal protection for owners of Title to Apartment Unit is able to extend Right of Building use above Right of Management